Case report: Novel SIN3A loss-of-function variant as causative for hypogonadotropic hypogonadism in Witteveen–Kolk syndrome - Correa Brito, Lourdes; Keselman, Ana; Villegas, Florencia; Scaglia, Paula; Esnaola Azcoiti, María; Castro, Sebastián; Sanguineti, Nora; Izquierdo, Agustín; Maier, Marianela; Bergadá, Ignacio; Arberas, Claudia; Rey, Rodolfo A.; et al. (Frontiers in Genetics, 2024)
Pubertal delay can be due to hypogonadotropic hypogonadism, which may occur in association with anosmia or hyposmia and is known as Kallmann syndrome (OMIM #308700). Recently, hypogonadotropic hypogonadism has been suggested to overlap with Witteveen-Kolk Syndrome (WITKOS, OMIM #613406) associated with 15q24 microdeletions encompassing SIN3A. Whether hypogonadotropic hypogonadism is due to haploinsufficiency of SIN3A or of any of the other eight genes present in 15q24 is not known. We report the case of a female patient with delayed puberty associated with intellectual disability, behaviour problems, dysmorphic facial features and short stature, at the age of 14 years. Clinical, laboratory and imaging assessments confirmed the diagnosis of Kallmann syndrome. Whole exome sequencing identified a novel heterozygous frameshift variant, NM_001145358.2:c.3045_3046dup, NP_001138830.1:p.(Ile1016Argfs*Ter6) in SIN3A, classified as pathogenic according to the ACMG/AMP criteria. Reverse phenotyping led to a clinical diagnosis of WITKOS. No other variant was found in 96 genes potentially related to hypogonadotropic hypogonadism. The analysis of the other contiguous 7 genes to SIN3A in 15q24 did not reveal any clinically relevant variant. In conclusion, these findings point to SIN3A as the gene in 15q24 related to the reproductive phenotype in patients with overlapping WITKOS and Kallmann syndrome.